Digitalisasi Keuangan Syariah: Pengaruh Kemudahan Penggunaan dan Literasi Keuangan terhadap Keputusan Pemanfaatan QRIS - Marnala Sitinjak; Eva Ulfah Rahayu; Masril Masril; Delvis Afrion (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
The shift toward digitalization is driving the public to adopt cashless payment systems, including the use of QRIS services provided by Sharia banking institutions. However, efforts to optimize these services face obstacles related to low financial literacy and concerns regarding platform practicality. This research analyzes the extent to which financial literacy and perceived ease of use influence the preferences of Pekanbaru residents regarding the use of Sharia bank QRIS. Employing a quantitative survey method, the study collected data from 96 respondents selected via purposive sampling. The data were analyzed using a multiple linear regression model. Partial tests revealed that financial literacy significantly impacts usage decisions (t = 7.798; Sig = 0.000), as does perceived ease of use (t = 3.372; Sig = 0.001). Simultaneous testing demonstrated that both independent variables collectively exert a significant influence on the decision to adopt Sharia bank QRIS (F = 46.607; Sig = 0.000). These findings confirm that the level of financial understanding and technological practicality are key determinants in the acceptance of Sharia-based digital financial services. Consequently, it is recommended that regulators and banking institutions intensify educational programs and expand the reach of Sharia QRIS facilities.